2005
DOI: 10.1093/sleep/28.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Etiology Is Associated with Symptom Onset During Sleep

Abstract: There are significant differences between stroke during sleep and stroke while awake concerning vascular risk profile and stroke etiologic subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…This is possibly related to the fact that such patients were not alert and were unable to express details of their stroke onset. The reason why this is not the case for sleeponset stroke may be that such strokes are more frequently lacunar [22]. Severe strokes were more frequent in patients with lower hemoglobin levels, suggesting that decreased oxygen transport capacity may increase infarct size, consistent with a previous report [23].…”
Section: Discussionsupporting
confidence: 85%
“…This is possibly related to the fact that such patients were not alert and were unable to express details of their stroke onset. The reason why this is not the case for sleeponset stroke may be that such strokes are more frequently lacunar [22]. Severe strokes were more frequent in patients with lower hemoglobin levels, suggesting that decreased oxygen transport capacity may increase infarct size, consistent with a previous report [23].…”
Section: Discussionsupporting
confidence: 85%
“…In a prospective study, 18% of patients with stroke of undetermined cause experienced symptoms during sleep which is consistent with our study. However the presence of PFO was not identified in that study [28]. The association of PFO and cerebrovascular events on awakening may be explained by several mechanisms.…”
Section: Symptoms and Clinical Features Of Pfo-associated Cerebrovascmentioning
confidence: 54%
“…BP is lower during the night and also falls following sexual intercourse. Interestingly, lacunar strokes, i.e., strokes involving small arterioles similar to those involved in NAION, occur substantially more often during sleep than during waking and this was the only stroke subtype in which this association was seen in that study [67]. Hayreh found that 73% of his 871 eyes with NAION occurred during sleep [68] and has proposed that nocturnal hypotension is a major but underappreciated precipitating risk factor for NAION [69].…”
Section: 3mentioning
confidence: 74%